Discovering 4-H Member Project Book - Joy Cantrell Jordan; Colleen Brown; Alisa Frye (EDIS)
Discovering 4-H Member Project Book (4H EXM 10) is a general club materials and organizational development publication for 4-H members ages 8–12. This project book gives an overall view of the many projects 4-H has to offer for those who are just starting 4-H. This book has many activities in all the different program areas. This document is  one of a series of the Family, Youth and Community Sciences Department, UF/IFAS Extension. Original publication date February 1992. Revised September 2005.